Social Preferences over Ordinal Outcomes - Ambuehl, Sandro; Bernheim, B. Douglas (American Economic Review, 2026)
We study social preferences in settings where someone who chooses on behalf of others knows how those individuals rank the available options but may lack cardinal information concerning those comparisons. Contrary to majoritarian principles, most people place more weight on preventing least preferred outcomes for others than on enabling most preferred outcomes. Ranks matter both intrinsically and because they provide a basis for inferring cardinal utility. Ordinal aggregation principles are stable across domains and countries with divergent political traditions. Designing attractive social choice mechanisms is challenging in practice partly because aggregation principles that make manipulation difficult yield outcomes people consider normatively unappealing. (JEL C91, D71, D72)